HOURS OF WORKING DAY AND CHOLESTEROL LEVEL IN LAND TRANSPORTATION DRIVERS IN A COMPANY IN LIMA - Requena, Reynaldo Ridan Martinez (2024)
Introduction: Ground transportation drivers face substantial risks to cardiovascular health, mainly hypercholesterolemia, possibly related to the hours of the workday.Objective. Determine the relationship between working hours and cholesterol level in land transport drivers in a company in Lima between the period from January 2022 to August 2023.Materials and methods. Correlational, cross-sectional research, which included 107 transport drivers. The main variables were: Hours of daily and weekly workday, total cholesterol and high-density lipoproteins (HDL), the instrument used was a data collection form. Spearman's Rho correlation test was used in the statistical analysis. The study was approved by the Ethics Committee of the Universidad Nacional Mayor de San Marcos.Results. It was observed that 47.02% of the workers worked between 9 and 10 hours a day, while 57.9% worked 61 to 72 hours a day. Furthermore, the majority of drivers had total cholesterol levels between 160 and 199 mg/dl (38.3%), and HDL cholesterol between 35 and 59 mg/dl (93.5%). A significant and direct correlation was determined between daily (p=0.026, Rho=0.216) and weekly (p=0.038, Rho=0.201) working hours with total cholesterol. No significant relationship was found with HDL cholesterol.Conclusions. It was identified that the hours of daily and weekly work hours were significantly related to the level of total cholesterol.